Comparison of the Effect of Two Different Abutment Diameters on Detorque Value Using Cyclic Loading and Thermocycling - E Jalalian; AR Banifatemeh; A Zarbakhsh; A Eskandari damaneh; E Hashemi; M Shariaty (Islamic Azad University, 2019)
Background and Aim: Screw loosening is a common problem with both screw-retained and cemented implant restorations. It is assumed that the abutment diameter affects detorque value and screw loosening. We aimed to determine the effect of two different abutment diameters on detorque value using cyclic loading and thermocycling. Materials and Methods: This in-vitro experimental study was conducted on sixteen Morse-taper implants (4×10 mm) with two different diameters (3.9 and 5.2 mm) installed with a 25-Ncm torque (n=8). Eight screws from each group (3.9- and 5.2-mm abutments) were maintained for a month in a stable state while the rest of the screws underwent cyclic loading for 10,000 cycles with the frequency of 1 Hz and force of 75 N/cm. Then, thermocycling was done at 5-55°C. Detorque value was determined using the torque meter used for screw tightening. Removal torque values were recorded. Maximum deformation force and fracture resistance were documented. Data were analyzed according to Student's t-test using SPSS 21.0 software. Results: Detorque values were 18.25±1.91 and 21.13±1.46 Ncm with 3.9- and 5.2-mm abutments, respectively. Detorque loss value was 15.50±5.83% with 5.2-mm abutment and 27±7.63% with 3.9-mm abutment. The mean difference between the two abutment diameters was 2.87±0.85 Ncm. Significant differences were observed on torque loss with 3.9-mm- compared to 5.2-mm-diameter abutments (P=0.004). Conclusion: The results suggested that torque loss was lower with 5.2-mm abutment diameter.